Luxury Tourism and Its Potential in the World A Bibliomatric Analysis - Sumadji, Rasya Agnela; Liani, Shahla Carissa; Kusumaningrum, Anisa Putri; Pradini, Gagih; Agustiani, Fitri (CV ODIS, 2023)
Luxury tourism research flourished in a few years. However, there are still few who provide a global picture of the concept. This study aims to identify the notion of luxury tourism and its potential in the world, such as source, author, and type of document. Bibliometric analysis was used to analyze 200 articles from Google Scholar published in 2023. Luxury tourism is the main keyword used in article titles, abstracts, and keywords to retrieve metadata from the Google Scholar bibliographic database, on Saturday, September 24, 2023. The tools used in bibliometric analysis are Microsoft Excel which is used to perform frequency analysis, VoS viewer for data visualization, and Harzing's Publish or Perish, which is used for citation and analysis metrics. This study's results show that most related articles are published in scientific journals, compared to others. Related articles published in scientific journals have obtained the highest citations compared to others. Articles are also found in English. Based on network visualization the most dominant terms (often appearing) are Luxury tourism and worldwide tourism. When viewed from the Overlay Visualization, the topic of